MODEL OF INFORMATION AND EDUCATIONAL ENVIRONMENT - Zabolotnya, Ю. В. (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the conceptual approaches to development of modern model of educational environment of higher education.